Review—Combining Experimental and Engineering Aspects of Catalyst Design for Photoelectrochemical Water Splitting. (11th August 2022) - Sharma, Chhavi; D., Pooja; Thakur, Anupma; Negi, Y. S.
Abstract : Hydrogen is one of the cleanest, most favourable, and most practical energy transferors. However, its efficient generation, storage and transportation are still a challenge. There are various routes available toward greener hydrogen. Solar-driven splitting is considered a cleaner method with no harmful emission and viability of up-scaling. Various semiconductors were studied for photo-electrochemical catalysis to improve overall efficiency of the system (i.e. Solar-to-Hydrogen (STH)). The insistence of framing this article is to offer an intense evaluation of scientific and technical aspects of available designing strategies' for photocatalysts and recent fruitful advancements towards product development. This review might act as a handbook for budding researchers and provide a cutting-edge towards innovative & efficient catalyst designing strategy to improve efficiency for working scientists.